Analysis of Factors Related to the Incident of Pneumonia in Toddlers in the Working Area of Pajar Bulan Community Health Center, Semende Darat Ulu District, Muara Enim Regency in 2022 - Eka Afrika; Andre Utama Saputa; Sri Handayani; Wahyu Ernawati; Muhammad Romadhon (MultiTech Publisher, 2023)
Pneumonia is very dependent on the daily behavior of the mother in taking action to prevent her toddler from contracting a dangerous disease. The aim of the study was to determine the relationship between mother's behavior and the incidence of pneumonia in toddlers in Pajar Bulan. From the Chi Square test results obtained p value (0.000) knowledge variable <α (0.05), attitude variable p value (0.000) <α (0.05), mother's action variable p value (0.181) <α (0, 05). These results can be interpreted that there is a significant relationship between knowledge, attitudes and actions of mothers regarding the incidence of pneumonia in the working area of ​​the Pajar Bulan Health Center, Semende Darat Ulu District, Muara Enim Regency.